Real superfoods : everyday ingredients to elevate your health - Robbins, Ocean, 1973-; Dandrea-Russert, Nichole (Hay House, Inc., 2023)
"When most people think of superfoods, they picture exotic and pricey products with magical healing abilities. But how "super" is a food that only a few can afford? Real superfoods are the ones that do the most good for the most people. They're loaded with nutrients, affordable, easy to find, and simple to prepare. When you know how to use them, they can taste amazing, and make you feel great. Ocean Robbins, co-founder and CEO of Food Revolution Network, and Nichole Dandrea-Russert, MS, RDN, show that the greatest superfoods on earth have been right under our noses all along. After reading Real Superfoods, you'll love leafy greens, mushrooms, legumes, berries, alliums, spices, sweet potatoes, nuts, seeds, coffee, and tea in a whole new way. Brimming with powerful disease-fighting nutrients, these superfoods can transform your health and bring new joy to your everyday cooking. For each type of superfood, complete with full-color pictures, you'll discover: · their health-promoting super powers · accessible ingredients, including some of our most common supermarket groceries · weekday-friendly cooking techniques · mouthwatering, easy-to-make recipes for every part of your day Embrace a lifetime of health and vitality with these super healthy and super delicious plant-based recipes!"--